Method for preparing high-compaction phosphate lithium battery positive electrode material by acid dissolution method

In the preparation of the positive electrode material of lithium phosphate battery by acid dissolution method, the iron source and manganese source are partially dissolved in the mixed acid to form a mixed system of solid particles and ionic states, which solves the problem of low compaction density of the positive electrode material in the prior art. , achieving the improvement of high compaction density and volume energy density, and simplifying the operation process.

CN119160866APending Publication Date: 2024-12-20WANHUA CHEM GRP BATTERY TECH CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310692956.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The compaction density of the existing lithium phosphate battery cathode material is low, which limits its volume energy density, and the existing improvement method is cumbersome to operate or difficult to commercially implement.

Method used

The iron source and manganese source are partially dissolved in the mixed acid by acid dissolving method to form a mixed system of solid particles and ionic states. Through the sintering process, a phosphate positive electrode material mixed with large and small particles is generated to improve compaction density and volume energy density.

Benefits of technology

The high compaction density and volume energy density of phosphate cathode materials have been improved, which simplifies the operating process and reduces production energy consumption and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004280793330000051
    Figure BDA0004280793330000051
  • Figure HDA0004280793340000011
    Figure HDA0004280793340000011
Patent Text Reader

Abstract

The invention provides a method for preparing a high-compaction phosphate lithium battery positive electrode material by an acid dissolution method, and an acid dissolution process is added in a pretreatment stage of a preparation process. The iron source and the manganese source are partially dissolved by adopting the mixed acid, so that the solid content of the slurry is reduced, the time of a subsequent sanding process can be shortened or the solid content of the sanding slurry is further improved, and the effects of improving the production efficiency and reducing the energy consumption are achieved. Meanwhile, the original pure solid iron source and manganese source are converted into a mixed system of a solid particle iron source / manganese source and an ionic state iron source / manganese source through acid dissolution treatment, and the reaction system has the advantages that in the sintering process, different reaction processes are directly carried out by utilizing raw materials in different states to form a product formed by mixing large and small particles, and the product quality is improved. And finally, the compaction density and the volume energy density of the phosphate positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a high-density phosphate lithium battery positive electrode material by an acid dissolution method, belonging to the field of lithium battery positive electrode material preparation. Background Art

[0002] Lithium-ion batteries have become the main development direction of portable energy storage and power batteries due to their high energy density, long service life, no memory effect, and high operating voltage. The positive electrode material is a key factor in determining the cost, safety, and electrochemical performance of lithium-ion batteries. Lithium iron phosphate / lithium iron manganese phosphate belongs to olivine-type lithium transition metal phosphates. Due to its outstanding advantages such as low cost, environmental friendliness, abundant raw material reserves, high safety, and stable operating voltage, it has become one of the current mainstream lithium battery positive electrode materials.

[0003] While the stable crystal structure of lithium iron phosphate / lithium manganese iron phosphate materials improves safety, they also have problems with low electronic conductivity and lithium ion mobility, which seriously affect their electrochemical performance, namely mass energy density. Through extensive research, researchers have significantly improved the mass energy density of phosphate cathode materials by using methods such as nano-sizing, carbon coating and element doping.

[0004] As electric vehicles have higher requirements for driving range, the energy density of phosphate cathode materials is challenged again. When the mass energy density is close to the theoretical value, further improving the volume energy density has become the focus of research. The important indicator for measuring volume energy density is the compaction density of powder. At present, the compaction density of commercial phosphate cathode materials is much lower than the theoretical density (about 3.6g / cm 3 ), among which the compaction density of lithium iron phosphate is mostly 2.35-2.6g / cm 3 The compaction density of lithium manganese iron phosphate is mostly 2.2-2.38g / cm 3 Therefore, there is huge room for improvement in the compaction density of phosphate positive electrode materials.

[0005] The existing technology mainly achieves high compaction of phosphate cathode materials by the following means: First, by controlling the particle size of sand milling, the product crystal size is different, thereby achieving high compaction. The operation process of this scheme is cumbersome, and the particle size distribution of the two sizes is low, often less than 2.6g / cm 3 , such as patents CN202111046942.X and CN202010117579.5. Second, by selecting iron phosphate raw materials with high and low iron-phosphorus ratios, the product size particles are mixed and compacted, such as patent CN201811397958.3. This solution has extremely high requirements for the selection of iron-phosphorus ratio of iron phosphate, and commercialization is difficult. Summary of the invention

[0006] In view of the above problems existing in the prior art, the present invention provides a method for preparing a high-density phosphate lithium battery positive electrode material by an acid dissolution method. The method utilizes the characteristic that the iron source and the manganese source are partially dissolved in the mixed acid, and the iron source and the manganese source are fully mixed and reacted with the mixed acid to form a reaction system of solid particle iron source / manganese source and ionic iron source / manganese source. During the sintering process, the solid particle iron source / manganese source generates a large particle phosphate positive electrode material through a solid phase reaction, and the soluble ionic iron source / manganese source first decomposes into nano-scale iron-manganese oxides during the sintering process, and then undergoes a solid phase reaction to generate a small particle phosphate positive electrode material. Finally, the compaction density of the phosphate positive electrode material is increased by mixing large and small particles, thereby increasing the volume energy density.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for preparing a high-density phosphate lithium battery positive electrode material by an acid dissolution method, the steps comprising:

[0009] 1) Mixing an iron source, a manganese source, a mixed acid and a solvent to form a slurry, and mixing them evenly by stirring and grinding to allow them to react fully;

[0010] Adding lithium source, carbon source and dopant into the slurry, grinding the solid particles in the slurry to nanometer level by sand milling, and then spray drying to obtain a precursor;

[0011] 2) The precursor is calcined in a nitrogen atmosphere and then crushed to obtain a high-density lithium phosphate battery positive electrode material.

[0012] In step 1) of the present invention, the iron source is selected from ferric phosphate and / or ferric phosphate dihydrate, wherein the iron-to-phosphorus ratio is 0.955-1:1, preferably 0.965-0.975:1;

[0013] The manganese source is selected from any one of manganese carbonate, trimanganese tetroxide, manganese dioxide, manganese oxalate, and manganese hydrogen phosphate, or a combination of at least two thereof, preferably any one of manganese carbonate, trimanganese tetroxide, and manganese hydrogen phosphate, or a combination of at least two thereof;

[0014] The mixed acid is selected from a combination of at least two of phosphoric acid, oxalic acid, citric acid, hydrochloric acid, sulfuric acid, and nitric acid, preferably, the molar proportion of oxalic acid in the mixed acid is ≥10% and ≤90%;

[0015] The lithium source is selected from lithium carbonate and / or lithium hydroxide;

[0016] The carbon source is selected from any one or a combination of at least two of glucose, sucrose, starch, polyethylene glycol, polyvinyl alcohol, and polyacrylic acid, preferably any one or a combination of at least two of glucose, sucrose, and polyethylene glycol;

[0017] The dopant is selected from any one or a combination of at least two of titanium oxide, niobium oxide, magnesium oxide, titanium tetrachloride, titanium sulfate, isopropyl titanate, and isobutyl titanate, preferably any one or a combination of at least two of titanium oxide, niobium oxide, and magnesium oxide;

[0018] In step 1) of the present invention, the molar ratio of the iron source to the manganese source, the mixed acid, the lithium source, and the dopant is 100: 0-400: 10-250: 50-510: 0.5-7.5. The amount of the carbon source added is 5-15wt% of the total weight of the solid material (referring to the total weight of the iron source, the manganese source, the lithium source, and the dopant);

[0019] The solvent is selected from water, ethanol or methanol; the amount of the solvent is such that the solid content of the slurry before sanding is 30-50wt%, preferably 35-45wt%.

[0020] In step 1) of the present invention, the stirring speed of the stirring mill is 100-200 rpm; the stirring time is 30-120 min;

[0021] The particle size of the slurry after sand grinding is controlled at D50 = 200-900nm, preferably 400-700nm;

[0022] The particle size of the precursor is controlled at D50=15-80 μm, preferably 30-60 μm.

[0023] In step 2) of the present invention, the nitrogen atmosphere has a nitrogen purity of ≥99.9995% and a pressure of 20-50 Pa. The calcination temperature is 750-800° C. and the holding time is 8-12 h.

[0024] The high-density phosphate cathode material prepared by the present invention has a particle size range of D10=0.3-0.5μm, D50=1-5μm, and D90≤5μm; for high-density lithium iron phosphate, the powder compaction density is ≥2.60g / cm 3 , the gram capacity of button battery is ≥156mAh / g (0.1C, 25℃); for high-density lithium manganese iron phosphate, the powder compaction density is ≥2.40g / cm 3 The gram capacity of the button battery is ≥148mAh / g (0.1C, 25℃).

[0025] The method of the present invention adds an acid dissolution process before the conventional sand milling process in the pretreatment stage of the preparation of the phosphate positive electrode material, and the iron source and the manganese source are fully mixed and reacted with the mixed acid through a stirred mill. This step utilizes the characteristics of the partial dissolution of the iron source and the manganese source in the mixed acid to form a mixed system of solid particle iron source / manganese source and ionic iron source / manganese source. The advantage of this reaction system is that during the sintering process, raw materials in different states undergo different reaction processes, thereby forming a product with large and small particles mixed. Specifically, the solid particle iron source / manganese source directly generates large particle phosphate positive electrode material through solid phase reaction during the sintering process, while the soluble ionic iron source / manganese source first decomposes into nano-scale iron and manganese oxides during the sintering process, and then undergoes solid phase reaction to generate small particle phosphate positive electrode material. Finally, a phosphate positive electrode material with large and small particles mixed is formed, which improves the compaction density and volume energy density.

[0026] Compared with the existing technology, the technical solution of the present invention has the following beneficial effects:

[0027] In the pre-treatment stage of the phosphate positive electrode material preparation process, the present invention adds an acid dissolution process, and uses mixed acid to partially dissolve the iron source and manganese source, thereby reducing the solid content of the slurry, shortening the time of the subsequent sand grinding process or further increasing the solid content of the sand grinding slurry, thereby improving production efficiency and reducing energy consumption. At the same time, after the acid dissolution treatment, the original pure solid iron source and manganese source are transformed into a mixed system of solid particle iron source / manganese source and ionic iron source / manganese source. The advantage of this reaction system is that different reaction processes are directly performed using raw materials in different states during the sintering process to form a product of large and small particles, which ultimately improves the compaction density and volume energy density of the phosphate positive electrode material.

[0028] Compared with physical blending or selecting different types of iron phosphate raw materials, this method has the characteristics of simple operation and high adaptability of raw materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the process of preparing high-density phosphate positive electrode materials by acid dissolution method. DETAILED DESCRIPTION

[0030] The present invention is now described as follows in conjunction with specific embodiments. It should be noted that the embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Any non-substantial improvements and adjustments made to the embodiments according to the content of the present invention are protected by the present invention.

[0031] The sources of the reagents and raw materials used in the examples and comparative examples of the present invention are as follows. The remaining reagents and raw materials are all common commercially available products unless otherwise specified:

[0032]

[0033] The test methods used in the embodiments and comparative examples of the present invention are as follows:

[0034] Particle size distribution: tested using Malvern MS3000.

[0035] Compaction density: tested using Sansi Test UTM7305.

[0036] Gram capacity (mass energy density) of button cell: button cell was prepared and tested using a Xinwei tester with a voltage range of 2.0V-3.75V.

[0037] Example 1

[0038] Preparation of high-density phosphate lithium battery positive electrode materials by acid dissolution method:

[0039] 1) Iron phosphate (100 mol), manganese carbonate (150 mol), mixed acid (150 mol phosphoric acid, 20 mol oxalic acid, 30 mol nitric acid) and water were mixed to prepare a slurry with a solid content of 40%. The slurry was mixed and fully reacted by a stirring mill at a speed of 200 rpm and a reaction time of 80 min.

[0040] 2) Add 128 mol of lithium carbonate, 5 mol of titanium dioxide and 8% of the total weight of glucose in the above slurry, then add water and mix to prepare a slurry with a solid content of 40 wt%, and grind it to a slurry with a D50 of 500 nm. Dry the sand-milled slurry through a spray drying device to obtain a precursor with a particle size of D50 of 40 μm.

[0041] 3) The precursor is transferred to a kiln in a nitrogen atmosphere (≥99.995%) and calcined at a furnace pressure of 30 Pa, a calcination temperature of 790° C., and a calcination time of 12 h to form a lithium manganese iron phosphate material through a solid phase reaction, which is then crushed to obtain a high-density lithium manganese iron phosphate.

[0042] The particle size of lithium manganese iron phosphate product is D10=0.41μm, D50=1.38μm, D90=3.32μm.

[0043] The powder compaction density of lithium manganese iron phosphate product is 2.41g / cm 3 The gram capacity (mass energy density) of the button battery 01C discharge is 156mAh / g (0.1C, 25℃).

[0044] Example 2

[0045] Preparation of high-density phosphate lithium battery positive electrode materials by acid dissolution method:

[0046] 1) Ferric phosphate (100 mol), mixed acid (20 mol oxalic acid, 30 mol nitric acid) and water were mixed to prepare slurry with a solid content of 40%. The slurry was mixed and fully reacted by stirring mill at a speed of 200 rpm and a reaction time of 80 min.

[0047] 2) Add 51 mol of lithium carbonate, 5 mol of titanium dioxide and 8% of the total weight of glucose in the above slurry, then add water and mix to prepare a slurry with a solid content of 40 wt%, and grind it to a slurry with a D50 of 500 nm. Dry the sand-milled slurry through a spray drying device to obtain a precursor with a particle size of D50 of 40 μm.

[0048] 3) The precursor is transferred to a kiln in a nitrogen atmosphere (≥99.995%) for calcination at a furnace pressure of 30 Pa, a calcination temperature of 790° C., and a calcination time of 12 h to form a lithium iron phosphate material through a solid phase reaction, which is then crushed to obtain high-density lithium iron phosphate.

[0049] The particle size of lithium iron phosphate product is D10=0.39μm, D50=1.32μm, D90=4.59μm.

[0050] The powder compaction density of lithium iron phosphate products is 2.68g / cm 3 The gram capacity (mass energy density) of the button battery 01C discharge is 160mAh / g (0.1C, 25℃).

[0051] Example 3

[0052] Preparation of high-density phosphate lithium battery positive electrode materials by acid dissolution method:

[0053] 1) Ferric phosphate (100 mol), mixed acid (20 mol oxalic acid, 30 mol nitric acid) and water were mixed to prepare slurry with a solid content of 38%. The slurry was mixed and fully reacted by stirring mill at a speed of 150 rpm and a reaction time of 120 min.

[0054] 2) Add 52 mol of lithium carbonate, 4 mol of titanium dioxide and 10% of the total weight of glucose in the above slurry, then add water and mix to prepare a slurry with a solid content of 38 wt%, and grind it to a slurry D50 = 400 nm. The sand-milled slurry is dried by a spray drying device to obtain a precursor with a particle size of D50 = 35 μm.

[0055] 3) The precursor is transferred to a kiln in a nitrogen atmosphere (≥99.995%) for calcination at a furnace pressure of 30 Pa, a calcination temperature of 780° C., and a calcination time of 12 h to form a lithium iron phosphate material through a solid phase reaction, which is then crushed to obtain high-density lithium iron phosphate.

[0056] The particle size of lithium iron phosphate product is D10=0.37μm, D50=1.11μm, D90=3.96μm.

[0057] The powder compaction density of lithium iron phosphate products is 2.62g / cm 3 The gram capacity (mass energy density) of the button battery 01C discharge is 161mAh / g (0.1C, 25℃).

[0058] Comparative Example 1

[0059] The method of Example 1 is referred to, except that the operation of step 1) is different: the iron phosphate and manganese carbonate in step 1) are directly added to step 2), and then processed to obtain a lithium manganese iron phosphate product.

[0060] The particle size of lithium manganese iron phosphate product is D10=0.31μm, D50=1.13μm, D90=4.89μm.

[0061] The powder compaction density of lithium manganese iron phosphate products is 2.25g / cm 3 The gram capacity (mass energy density) of the button battery 01C discharge is 145mAh / g (0.1C, 25℃).

[0062] Comparative Example 2

[0063] The method of Example 1 is referred to, except that the molar amount of the mixed acid in step 1) is increased proportionally to 1.5 times, namely 225 mol of phosphoric acid, 30 mol of oxalic acid, and 45 mol of nitric acid, and then treated to obtain the lithium manganese iron phosphate product.

[0064] The particle size of lithium manganese iron phosphate product is D10=0.38μm, D50=1.44μm, D90=5.63μm.

[0065] The powder compaction density of lithium manganese iron phosphate products is 2.35g / cm 3 The gram capacity (mass energy density) of the button battery 01C discharge is 121mAh / g (0.1C, 25℃).

[0066] Comparative Example 3

[0067] The method is similar to that of Example 2, except that the mixed acid in step 1) is replaced with 50 mol oxalic acid.

[0068] The final performance of the lithium iron phosphate product is as follows:

[0069] The particle size of lithium iron phosphate product is D10=0.35μm, D50=1.02μm, D90=3.99μm.

[0070] The powder compaction density of lithium iron phosphate products is 2.45g / cm3 The gram capacity (mass energy density) of the button battery 01C discharge is 159mAh / g (0.1C, 25℃).

[0071] Comparative Example 4

[0072] The method is similar to that of Example 2, except that the mixed acid in step 1) is replaced with 50 mol phosphoric acid.

[0073] The final performance of the lithium iron phosphate product is as follows:

[0074] The particle size of lithium iron phosphate product is D10=0.64μm, D50=1.92μm, D90=7.23μm.

[0075] The powder compaction density of lithium iron phosphate products is 2.75g / cm 3 The gram capacity (mass energy density) of the button battery 01C discharge is 138mAh / g (0.1C, 25℃).

[0076] Comparative Example 5

[0077] The method is similar to that in Example 2, except that the mixed acid in step 1) is replaced with 3 mol of oxalic acid and 47 mol of nitric acid.

[0078] The final performance of the lithium iron phosphate product is as follows:

[0079] The particle size of lithium iron phosphate product is D10=0.36μm, D50=1.34μm, D90=4.13μm.

[0080] The powder compaction density of lithium iron phosphate products is 2.50g / cm 3 The gram capacity (mass energy density) of the button battery 01C discharge is 160mAh / g (0.1C, 25℃).

Claims

1. A method for preparing a high-density phosphate lithium battery positive electrode material by acid dissolution, characterized in that the steps include: 1) Mixing an iron source, a manganese source, a mixed acid and a solvent to form a slurry, and mixing them evenly by stirring and grinding to allow them to react fully; Adding lithium source, carbon source and dopant into the slurry, grinding the solid particles in the slurry to nanometer level by sand milling, and then spray drying to obtain a precursor; 2) The precursor is calcined in a nitrogen atmosphere and then crushed to obtain a high-density lithium phosphate battery positive electrode material.

2. The method according to claim 1, characterized in that In step 1), the molar ratio of the iron source to the manganese source, the mixed acid, the lithium source, and the dopant is 100:0-400:10-250:50-510:0.5-7.

5.

3. The method according to claim 1 or 2, characterized in that: In step 1), the iron source is selected from ferric phosphate and / or ferric phosphate dihydrate, wherein the iron-to-phosphorus ratio is 0.955-1:1; and / or The manganese source is selected from at least one of manganese carbonate, manganese tetraoxide, manganese dioxide, manganese oxalate and manganese hydrogen phosphate; and / or The lithium source is selected from lithium carbonate and / or lithium hydroxide; and / or The dopant is selected from at least one of titanium oxide, niobium oxide, magnesium oxide, titanium tetrachloride, titanium sulfate, isopropyl titanate, and isobutyl titanate.

4. The method according to any one of claims 1 to 3, characterized in that: In step 1), the mixed acid is selected from a combination of at least two of phosphoric acid, oxalic acid, citric acid, hydrochloric acid, sulfuric acid, and nitric acid. Preferably, the molar ratio of oxalic acid in the mixed acid is ≥10% and ≤90%.

5. The method according to any one of claims 1 to 4, characterized in that: In step 1), the carbon source is selected from at least one of glucose, sucrose, starch, polyethylene glycol, polyvinyl alcohol, and polyacrylic acid; Preferably, the amount of carbon source added is 5-15 wt % of the total weight of the solid material.

6. The method according to any one of claims 1 to 5, characterized in that: In step 1), the solvent is selected from at least one of water, ethanol or methanol; Preferably, the amount of the solvent used is such that the solid content of the slurry is 30-50 wt %.

7. The method according to any one of claims 1 to 6, characterized in that: In step 1), the stirring speed of the stirring mill is 100-200 rpm, and the stirring time is 30-120 min; The particle size of the slurry after sand grinding is controlled at D50 = 200-900nm, preferably 400-700nm; The particle size of the precursor is controlled at D50=15-80 μm, preferably 30-60 μm.

8. The method according to any one of claims 1 to 7, characterized in that: In step 2), the nitrogen atmosphere has a nitrogen purity of ≥99.9995% and a pressure of 20-50Pa.

9. The method according to any one of claims 1 to 8, characterized in that: In step 2), the calcination temperature is 750-800° C. and the time is 8-12 hours.

10. A high-density phosphate cathode material prepared according to the method of any one of claims 1 to 9, characterized in that: The particle size range is D10=0.3-0.5μm, D50=1-5μm, D90≤5μm.

Citation Information

Patent Citations

  • Preparation method of phosphate positive electrode material

    CN114516626A

  • Nanocrystalline lithium iron manganese phosphate precursor as well as preparation method and application thereof

    CN115626622A